“What are the traces of a festival?” : Expanded Dramaturgies of Curating “Different Narratives” – Baltic Circle - Trencsényi, Katalin (International Association of Theatre Critics, 2025)
Building on Marianne Van Kerkhoven’s ideas about micro and macro dramaturgy, this writing expands the notion of (festival) curating beyond staging performances and shaping a repertoire, and examines how festivals are creating “cultural gathering spaces” (J. Applebaum), “assemblages” (A. Lowenhaupt Tsing), and “spaces for dialogue” (H. Parry) outside the walls of their building, venturing into site-responsive, process-focussed, and interdisciplinary practices. To illustrate this move from product to process, from consumption of art to civil participation in local issues of concern, the essay presents, analyses, and frames the Wild Trippers project (2020-2024) of Baltic Circle International Theatre Festival within a dramaturgical-curatorial context. Based on research interviews with Taru Elfving, Helsinki-based contemporary art curator, Trevor Davis, director of Metropolis (Copenhagen),and Hanna Parry, artistic director of Baltic Circle, the essay seeks to find out what the guiding ideas and principles behind this new way of working are and how site-sensitive work can be contextualised within an art festival.
Keywords: dramaturgia; teatteriala; festivaalit